Analysis of economic and agricultural indicators under sustainable agriculture conditions with the use of Bayesian modelling - Grotkiewicz, Katarzyna (Technical Sciences, 2017)
Searching for relations between the level of production intensity, land efficiency and work performance, comparative analyses were carried out on international scale taking into consideration 45 countries from around the world with the use of the Statistical Yearbook (2013) and International Statistics Yearbook (2015). The research covered basic qualification criteria of sustainable agriculture, i.e. the level of mineral fertilization and stocking density as well as productivity rates, i.e. land efficiency and work performance and factors which shape them. The main aim of the research is the use of Bayesian modelling in order to predict the development of various economical and agricultural indicators and also show relationships between events basing on the theory of probability.